Characterization of perfluorocarbon relaxation times and their influence on the optimization of fluorine‐19 MRI at 3 tesla. Issue 6 (6th July 2016) - Colotti, Roberto; Bastiaansen, Jessica A. M.; Wilson, Anne; Flögel, Ulrich; Gonzales, Christine; Schwitter, Juerg; Stuber, Matthias; van Heeswijk, Ruud B.
Abstract : Purpose: To characterize and optimize 19 F MRI for different perfluorocarbons (PFCs) at 3T and quantify the loss of acquisition efficiency as a function of different temperature and cellular conditions. Methods: The T1 and T2 relaxation times of the commonly used PFCs perfluoropolyether (PFPE), perfluoro‐15‐crown‐5‐ether (PFCE), and perfluorooctyl bromide (PFOB) were measured in phantoms and in several different conditions (cell types, presence of fixation agent, and temperatures). These relaxation times were used to optimize pulse sequences through numerical simulations. The acquisition efficiency in each cellular condition was then determined as the ratio of the signal after optimization with the reference relaxation times and after optimization with its proper relaxation times. Finally, PFC detection limits were determined. Results: The loss of acquisition efficiency due to parameter settings optimized for the wrong temperature and cellular condition was limited to 13%. The detection limits of all PFCs were lower at 24 °C than at 37 °C and varied from 11.8 ± 3.0 mM for PFCE at 24 °C to 379.9 ± 51.8 mM for PFOB at 37 °C. Conclusion: Optimizing 19 F pulse sequences with a known phantom only leads to moderate loss in acquisition efficiency in cellular conditions that might be encountered in in vivo and in vitro experiments. Magn Reson Med 77:2263–2271, 2017. © 2016 International Society for Magnetic Resonance in Medicine